Cytomegaloviral colitis in HIV positive patients: endoscopic findings - Marques Jr,Oswaldo (2007)
BACKGROUND: Diarrhea in seropositive human immunodeficiency virus patients is one of the most important and disabling symptoms, and often decreases their quality of life. Cytomegalovirus colitis is among the principal causes of this symptom and colonoscopy is the gold standard examination to diagnose it. AIM: To define the main endoscopic findings in seropositive human immunodeficiency virus patients with cytomegalovirus colitis. METHODS: Two hundred and forty-three colonoscopies were performed in 200 seropositive human immunodeficiency virus patients with diarrhea associated or not to abdominal pain or gastrointestinal bleeding, over 10-year period, whom 51 patients were diagnosed with cytomegalovirus colitis. Full length colonoscopy with ileum intubation was always tried and multiple biopsies of all segments examined, including endoscopically normal segments, were attempted. All diagnoses were confirmed by histologic and immunohistochemical studies. RESULTS: Total colonoscopy was possible in 98.03% and ileum intubation in 88.23% of these cytomegalovirus colitis patients. At colonoscopy, a heterogeneous ulcerative pattern was presented in 72.54%, an inflammatory process of the mucosa in 21.56% and 5.88% of the patients mucosa was endoscopically normal. CONCLUSION: Full length colonoscopy with ileum intubation and multiples biopsies of all segments, even when they are endoscopically normal, have always to be attempted in cases of seropositive human immunodeficiency virus patient with diarrhea.